Die Macht der Gefühle (1983) & Serpentine Gallery Program (1995-2000) - Kluge, Alexander (München : Edition Filmmuseum, 2007)
Die Macht der Gefühle: Explains that emotion isn’t to be confused with sentimentality. In this intellectual perspective of what emotion is and does, young couples run into difficulties as they try to translate their experiences of love into clear decision-making. A woman who has shot her husband provides a judge with a puzzle. Those who love can bring the dead back to life by means of co-operation. Serpentine Gallery Program: A collection of short experimental films created by Alexander Kluge. ## Disc 1. Die Macht der Gefühle = The Power of emotion / ein Film von Alexander Kluge ; [Kamera], Werner Lüring, Thomas Mauch (112 min., 1983) -- Disc 2. Serpentine Gallery program / Drehbuch und Regie, Alexander Kluge (100 min., 1995-2005). Minutenfilme = Minute Films ; Der flexible Unternehmer = The flexible entrepreneur ; Die Liebe stört der kalte Tod = Cold death Interrupts love ; Wer immer hofft, stirbt singend = He who hopes dies singing ; Eine Frau wie ein Vulkan = A woman like a volcano ; Der Offizier als Philosoph = The Officer as a Philosopher.
Onderzoek KASK Professioneel (OFVP)
Duits gesproken, ondertitels in Engels, Frans, Russisch, Chinees en Spaans
film
Keywords: Kluge, Alexander